Molecular imaging of pancreatic ductal adenocarcinoma - Wei Huang; Gang Huang; Shuxian An; Jianjun Liu (View, 2023)
Abstract Pancreatic ductal adenocarcinoma (PDAC), a deadly cancer characterized by multiple molecular alterations, remains the most lethal cancer, with a 5‐year survival rate of about 3–15%. Early diagnosis and treatment monitoring are essential to improve patient survival. Traditional imaging methods can only provide structural information, but not biological processes. Nuclear medicine imaging combines the high sensitivity of radionuclides with high‐resolution structural imaging to visualize specific targets of PDAC for more accurate and reliable diagnosis and monitoring of therapeutic responses. In this review, we summarize the available literature regarding molecular nuclear medicine imaging in PDAC. We classify the probe targets into two categories, targeting tumor cell membranous and the tumor microenvironment, respectively. We summarize the latest evidence in this field and outline how these emerging strategies could potentially optimize clinical practice.